Energy use of biogas through chemical looping technologies with low-cost oxygen carriers. (15th July 2023) - Cabello, Arturo; Mendiara, Teresa; Teresa Izquierdo, M.; García-Labiano, Francisco; Abad, Alberto
Highlights: FS_GR Fe-based residue tested in continuous unit for biogas CLC and CLR. CH4 combustion efficiency outperformed those for other low-cost Fe-based materials. FS_GR performed the dry-reforming of biogas with high selectivity to CO and H2. FS_GR showed chemical/mechanical stability even with high degree of reduction. Downstream CO2 separation, H2 purification and CH4 recirculation proposed for CLR. Abstract: Biogas is a renewable fuel generated in the anaerobic digestion of organic material. The expansion of biogas as a bioenergy source in the next decades leads to find new ways for its energy exploitation such as the Chemical Looping technologies. In this work, a low-cost Fe-based residue was used as oxygen carrier in two processes with biogas, namely Chemical Looping Combustion (CLC) and Chemical Looping Reforming (CLR). CLC process is focused on the energy production with CO2 capture. CLC experiments showed higher methane combustion efficiency (∼86%) than those referred in literature with other low-cost Fe-based materials. CLR process is dedicated to the production of syngas or hydrogen without CO2 emissions. Ni- or Cu-based oxygen carrier had been successfully used in order to catalyse the methane reforming. Here, the Fe-based material was also used for CLR. The biogas composition facilitated dry reforming of biogas to obtain syngas. In the dry-CLR of biogas, it was possible to reach about 55% methane conversion with a yield to syngas of 1.3 mol (CO + H2 )/mol CH4 . A suitable management of the effluent gas is proposed to maximize CH4 conversion and syngas yield, which includes CO2 separation, H2 purification and CH4 recirculation. Both results confirm the potential of the energy use of biogas under these technologies and the promising results with the new oxygen carrier developed.